2017
DOI: 10.1038/srep44491
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes of the Mediterranean Sea ecosystem: modelling the role and impact of primary productivity and fisheries changes over time

Abstract: The Mediterranean Sea has been defined “under siege” because of intense pressures from multiple human activities; yet there is still insufficient information on the cumulative impact of these stressors on the ecosystem and its resources. We evaluate how the historical (1950–2011) trends of various ecosystems groups/species have been impacted by changes in primary productivity (PP) combined with fishing pressure. We investigate the whole Mediterranean Sea using a food web modelling approach. Results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 78 publications
(165 reference statements)
15
96
1
1
Order By: Relevance
“…Overall, our input data respected the general rules/principles of ecosystem ecology (Link, 2010), similar to other studies (Bentorcha et al, 2017;Piroddi et al, 2017), except for the observed positive relationship between the production/consumption and trophic level. In our case, this effect was mainly caused by four compartments: the gastropod, mullet, sardine, and snook.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…Overall, our input data respected the general rules/principles of ecosystem ecology (Link, 2010), similar to other studies (Bentorcha et al, 2017;Piroddi et al, 2017), except for the observed positive relationship between the production/consumption and trophic level. In our case, this effect was mainly caused by four compartments: the gastropod, mullet, sardine, and snook.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…de Juan et al 2007). This increase in fishing pressure has led to the over-exploitation of fish stocks and a shift in community structures (Coll et al 2010;Piroddi et al 2017). The Mediterranean Sea has many entry routes for exotic species due to the opening of the Suez Canal, high maritime traffic and aquaculture activity (Katsanevakis et al 2014;Mačić et al 2018).…”
Section: Drivers and Pressuresmentioning
confidence: 99%
“…Existing literature shows that biodiversity, ecological functions and related ecosystem services in the Mediterranean Basin terrestrial (Bangash et al 2013;Doblas-Miranda et al, 2015;Thom and Seidl 2016), freshwater (Mediterranean Wetland Observatory 2018) and marine ecosystems (Coll et al 2010(Coll et al , 2012Piroddi et al 2017) are often threatened by a series of indirect drivers and direct pressures, which may lead to a decline in the capacity of ecosystems to provide services (Bangash et al 2013;Piroddi et al 2017). Recent changes within the Mediterranean Basin such as the abandonment of agrosilvopastoral practices, the intensification of primary sector activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, for instance, no biological information 764 for as many as 43 % of the Mediterranean fish species (Dimarchopoulou et al, 2017). The lack of 765 biological and ecological data for a large number of species as well as the quality of commercial 766 fisheries data, especially in the southern and eastern parts of the Mediterranean Sea, are 767 hindrances to reliable stock assessments, to the development of more integrated ecosystem 768 models, and thus to the implementation of an effective ecosystem-based management to achieve 769 good environmental status in the Mediterranean Sea (Coll et al, 2013;Piroddi et al, 2015aPiroddi et al, , 2017. 770 A crucial challenge is to increase the number of assessed stocks in order to ensure their 771 sustainable exploitation in a first step, to allow the parameterization and calibration of more 772 integrated ecosystem models that would support the development of ecosystem-based fisheries 773 management at the Mediterranean basin scale in a second (Cardinale and Scarcella, 2017;Coll et al, 2013;Colloca et al, 2013).…”
Section: Emerging Spatial Patterns 655mentioning
confidence: 99%